Etika Guru Pendidikan Agama Kristen dan Signifikansinya Pada Pembentukan Karakter Siswa - Haposan Simanjuntak; Yuniarti Y; Frilia Kartini Sipahutar; Delvi Hutapea; Meliana Agustina Simanjuntak; Mika Manalu; Yohana Siburian (Madani: Jurnal Ilmiah Multidisiplin, 2023)
Forming the character of students today is the main task of a teacher as a parent and main educator at school. Thus, the aim of writing this article is to shape the character of students based on Christian values through the ethics applied by Christian religious education teachers to students. The method used in writing this article is a descriptive qualitative method using library literature which contains sources from articles, books and website pages that support the topic of this article and can be justified academically. In the process the author reads, studies and processes the selected materials according to exact needs. The result of this article is that students can implement the correct attitudes or ethics based on real examples from a PAK teacher. So that students become individuals with correct character based on Christian values. This is of course based on the ethics and attitudes carried out by Christian religious education teachers for each student.